Necrolytic Migratory Erythema as the First Manifestation of Glucagonoma - Abolfazl Afsharfard; Khashayar Atqiaee; Saran Lotfollahzadeh; Majid Alborzi; Amir Derakhshanfar (Case Reports in Surgery)
Necrolytic migratory erythma (NME) as a rare skin disorder that can affected Perineum, distal extremities, lower abdomen and face are the most commonly affected sites.It can be as a part of Glucagonoma syndrome that is defined as an association of glucagonoma with NME, hyperglucagonemia, glucose intolerance, anemia and weight loss. Here, Authors describe a woman admitted to the dermatology ward with NME which was later found to be associated with glucagonoma and multiple hepatic lesions.